2022
DOI: 10.3389/fpsyt.2022.830081
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Probiotics and Anxiety and Depression Levels in Cancer Patients: A Retrospective Cohort Study

Abstract: ObjectiveStudies have shown a correlation between gut microbiota and anxiety and depression levels. However, these studies are mainly animal studies or clinical studies of non-cancer patients, there is still a lack of relevant studies in cancer patients. The main objective of this trial was to analyze the correlation between probiotics and anxiety and depression levels in cancer patients.MethodsWe screened all cancer patients consecutively admitted to the inpatient department of the First Affiliated Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Anxiety and depression: Anxiety was measured using the Hamilton anxiety scale (HAMA)[ 11 ] and depressive mood was measured using the Hamilton depression scale (HAMD)[ 12 ]. The HAMA has a total of 14 questions, involving a five-level scoring method ranging from 0 to 4 points, with a total score between 0 and 56 points.…”
Section: Methodsmentioning
confidence: 99%
“…Anxiety and depression: Anxiety was measured using the Hamilton anxiety scale (HAMA)[ 11 ] and depressive mood was measured using the Hamilton depression scale (HAMD)[ 12 ]. The HAMA has a total of 14 questions, involving a five-level scoring method ranging from 0 to 4 points, with a total score between 0 and 56 points.…”
Section: Methodsmentioning
confidence: 99%
“…Anxiety levels in patients with enterostomy were assessed using the HAMA, [10] while depressed mood was measured using the Hamilton Depression Scale (HAMD). [11]…”
Section: Methodsmentioning
confidence: 99%
“…Based on prior studies ( 29 , 30 ), we identified potential confounders, including age, sex, marital status, educational level, household income, lifestyle (smoking status, drinking status, aerobic exercise, and anaerobic exercise), daily energy intake, and body mass index (BMI). Participants were also classified by educational level as follows: less than elementary school, middle school, high school, and college or more.…”
Section: Methodsmentioning
confidence: 99%